STUDI FLUKS KARBON DIOKSIDA PADA BERBAGAI TIPE PENGGUNAAN DI LAHAN GAMBUT PASANG SURUT DAN PEDALAMAN : Yosep1), Y.Sulistianto2), Adi Jaya2) 1)Fakultas Pertanian Universitas Palangka Raya - JHT, Admin (Jurnal Hutan Tropika, 2016)
ABSTRACK The aim of this study to known influence land use change in low tide and ombrotrophic peatland on forest land, ex-burns land, rubber tree land, and maize land and to known amount of microbial populations there. Data was recorded automatically by some equipments are chamber, Infrared CO2 analyzer (Fuji ZFP9GC11), injection 200 cc, Soda Lime, Vacuum plastic, Vacuum oven, termometer, FDR ML 2 Theta Probe Delta Y Device Co, Sensor water table, Lux meter, meter, camera, and paper label. Observation method was carried out at the village Kalampangan (ombrotrophic peatland) , district of Sebangau, Palangka Raya city, and at the village Purwodadi (low tide peatland), district of Maliku, Pulang Pisau Regency, starting from May up to July 2014. Observation variables consist of CO2 fluxes, fluctuations of groundwater levels, soil temperature, soil humidity and microbial populations. The results show that overall carbon dioxide fluxes higher in low tide peatland, with the highest fluxes in burnt areas, 430.24 mg C m-2 h-1, whereas in Ombrotrophic peatland, the highest on 292 forested land, 92 mg C m-2h-1. In Ombrotrophic peatland, relation between fluxes of carbon dioxide and the soil temperature is significant in the burnt areas with a value of R = 0.856 with a quadratic pattern, with the average temperature of 28.89 Â° C. Fluxes of carbon dioxide significantly effected by soil moisture that is at a rubber plantation with a value of R = 0.640 with quadraticpatterned, average soil moisture of 0.61 m3/m-3. Fluxes of carbon dioxide to the groundwater depth is significant on a rubber plantation with a value of R = 0.872 with a quadratic pattern, and depth of groundwater on average of 83.74 cm. The populatuin of microorganisms, in forest land 137 sel/ml, rubber plantations 154 sel/ml, cornfields 157 sel/ml and ex-burnt is 80 sel/ml. In Low Tide peatland, fluxes of carbon dioxide to the soil temperature is significant in forest land with the value of R = 0.545 with cubic pattern, and the average temperature of 27,39 oC. Soil moisture has the siginificant effect to fluxes of carbon dioxide that is in the burnt areas with a value of R = 0.617 with patterned quadratic, and average soil moisture of 0.50 m3/m-3. The ground water depth has a siginificant effect to fluxes of carbon dioxide in a cornfield with a value of R = 0.743 with a quadratic pattern, and the depth of soil water on average of 68.98 cm. Population of soil microorganisms, in forest land 73 sel/ml, rubber plantations 36 sel/ml, cornfields 51 sel/ml and ex-burnt 18 sel/ml. Soil temperature, soil moisture, groundwater depth and microoganisms effect on carbon dioxide fluxes. Key words: Carbon dioxide, fluxes, microorganisms, peatland